The psychosomatics attributes in Plato’s Timaeus and Charmides: disease and health of man - Araújo, Hugo Filgueiras de (Argumentos - Revista de Filosofia, 2023)
The paper analyzes in Plato the integration/συναμφότερον between the human soul and body in Charmides and Timaeus exploring the ideas of health/ὑγίεια and disease/νόσος and how they originate in man. The thesis is that in Plato’s thought there is a strong presence of an integrated view of man, the relationship between the constitutive instances (soul and body) being psychosomatic, since both suffer (πάσχω) influence from each other. The nuances of the soulbody relationship are also considered with regard to the psychophysical aspects of this compound. As a consequence, it goes beyond the dualistic interpretation erroneously propagated by philosophy manuals, which insist that in Plato the soul must despise the body. In other words, what “seems” in Plato’s texts to be a reference to a strong tension between soul and body is in fact a warning by the philosopher of the need for a balanced integration between both.